Post-Traumatic Septic Bone Sequestration in Three Dogs - Hayes, Graham; Harris, Karen; Langley-Hobbs, Sorrel (VCOT Open, 2019)
Formation of discreet bony sequestra is reported in three dogs presenting with post-traumatic osteomyelitis with no previous history of orthopaedic surgery. Two cases had a presumed or confirmed history of dog bites, while the third case had a fracture treated conservatively. All three were treated with surgical debridement and sequestrectomy with good outcome.
Keywords: osteomyelitis; bone diseases; infections